1998
DOI: 10.1177/0146167298245001
|View full text |Cite
|
Sign up to set email alerts
|

Causal Uncertainty: Factor Structure and Relation to the Big Five Personality Factors

Abstract: Two studies provide construct validity evidence for the Causal Uncertainty Scale. In the first study, the factor structure of the CUS was validated. Exploratory and confirmatory factor analyses indicated that the CUS is composed of two highly correlated factors, uncertainty about the causes of one's own outcomes and uncertainty about the causes of others' outcomes. Relationships between these two factors and a variety of other variables were assessed. In the second study, the relationship between the CUS, its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 51 publications
1
22
0
1
Order By: Relevance
“…In the 2-factor model, the CU items loaded on a single CU factor. In the 3-factor model, the CU items loaded on two factors (own and other outcomes) that were positively correlated, r = .57, replicating the patterns reported by Edwards et al (1998).…”
Section: Pilot Studysupporting
confidence: 55%
See 2 more Smart Citations
“…In the 2-factor model, the CU items loaded on a single CU factor. In the 3-factor model, the CU items loaded on two factors (own and other outcomes) that were positively correlated, r = .57, replicating the patterns reported by Edwards et al (1998).…”
Section: Pilot Studysupporting
confidence: 55%
“…Prior factor analyses of the CUS have revealed that it consists of two highly correlated factors: CU about one's own and other people's outcomes (Edwards, Weary, & Reich, 1998). We wanted to see if the CI items would form a third distinct factor.…”
Section: Pilot Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Sample items from the scale include: "When I receive poor grades, I usually do not understand why I did so poorly"; "When I see something good happen to others, I often do not know why it happened"; and "I often feel like I do not have enough information to come to a conclusion about why things happen to me." The scale has been shown to have high internal consistency (Cronbach's a = .83) and a 6-week test-retest reliability from .62 to .80 (see Reich, 1998, andEdwards, 1994, for reviews of the psychometric and construct validation evidence for this scale).The mean CUS score in the current study was 38.87 (SD = 10.28). To determine whether participants in the two stereotype conditions differed in terms of their level of causal uncertainty, their CUS scores were regressed on the stereotype information condition variable (effects coded so that the stereotype condition = 1 and the no-stereotype condition = -1).…”
mentioning
confidence: 60%
“…Belirsizliğin özel bir durumunu inceleyen nedensel belirsizlik kuramı (Causal Uncertainty Theory) (Weary ve Edwards, 1994, 1996 kişilerin neden sonuç ilişkisini atfedebilme becerisinden şüphe etmesi ile ilgilenmektedir. Çalışmaların sonuçlarına göre nedensel belirsizlik ile olumsuz duygu durumu (Tobin ve Raymundo, 2010), depresyon (Weary ve Edwards, 1994;1996), nörotiklik (Edwards, Weary ve Reich, 1998) ve onay arama ihtiyacı (Jacobson ve Weary, 1999;Jacobson, 2007) (Hogg, 2009;Hogg ve Abrams, 1993). Gruplar kişiye hem kendini ve iç grup üyelerini tanımlaması hem de kendini dış grup üyelerinden ayrıştırması için fırsat sunar (Hogg, 2009).…”
Section: Belirsizliğin Etkileri Nelerdir?unclassified